Analysis of flow dynamics around two rotating circular cylinders in tandem and side by side - Silva, Alice Rosa da; Lima, Antônio Marcos Gonçalves de (International Journal of Advanced Engineering Research and Science, 2020)
In this paper, the flow dynamics around two rotating circular cylinders arranged in two different configurations, in turbulent and laminar regimes are analyzed through the Immersed Boundary Methodology. The Large Eddy Simulation with dynamic Smagorinsky sub-grid scale is also used here. For the side by side and in tandem configurations, the simulations are performed, for Re 100, specific rotation 0.5 and spacing ratio varying between 1.5 and 5.0. For the first arrangement, simulations are also carried out, for Re and spacing ratio constant, and the specific rotation varying between 0 and 2. For in tandem configuration, the Re ranges from 200 to 105 and the others parameters are maintained constant. The results showed that the cylinder arrangements, in addition to the mentioned parameters, play an important role in the mechanism of the vortex shedding, as well as in the wake pattern and in the fluctuations of drag and lift coefficients. The rotation mechanism inhibits the vortex shedding process for different values of spacing ratio depending on the arrangement of the cylinders. Vorticity contours, time evolutions of fluid dynamics coefficients as well as pressure distribution along the cylinder are presented.